Cultivation in an Alpine Region: Implications for Soil Bacteria - Xiaomin Huang; Jingtao Shi; Wenyuan Sun; Chengming Sun; Xinping Shen (Agronomy, 2023)
Land use change is a major predictor for variations in soil bacteria, which plays a key role in maintaining soil multifunctionality and function of terrestrial ecosystems. The effects of land use change on the soil bacterial community in an alpine region at the Qinghai-Tibetan Plateau (QTP) were still unclear. In this study, we investigated soil bacterial profiles under grazed grassland, enclosed grassland, continuous cropland, rotation cropland and abandoned cropland in the Tianzhu alpine agro-pastoral ecotone. Our results showed that Proteobacteria, Acidobacteria and Actinobacteria were the most three abundant phyla regardless of land use change, accounting for over 60% of the total. Cultivation declined soil bacterial alpha diversity without recovering even after abandonment. Over 73% variations in bacterial diversity can be explained by soil physical and chemical properties. In addition, soil moisture could be the main driver for the difference in bacterial structure between croplands and others. Soil bulk density, pH, organic carbon and total nitrogen contents seem to be the key factors determining the difference in bacterial structure between abandoned croplands and others. Our results have implications for comprehensive understanding about the responses of the soil bacterial community to land use change in alpine regions.